The Effect of Adding Sugarcane Bagasse Ash on Water Absorption, Compressive Strength, and Fracture of Concrete Blocks - Marjuki Marjuki; Dwiria Wahyuni; Asifa Asri (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Concrete block is a material that can be strengthened by utilizing silica from natural materials such as bagasse. Silica (SiO2) in bagasse can be enriched through a high-temperature combustion process. This study aims to see the effect of adding bagasse ash (AAT) as a filler on water absorption, compressive and fracture strength of concrete blocks. Bagasse is first burned in a drum at a temperature of 320 ℃ for 1 hour. The results of the burning of bagasse are sieved using 50 and 150 mesh sieves, then characterized using XRF. The results of the study obtained a silica content of 30%, the highest water absorption of 10.6% in bricks without the addition of AAT and the lowest in bricks with the addition of 150 mesh AAT, which is 7.66%. Concrete blocks with AAT size 150 mesh have the highest density, compressive and fracture strength of 2079.99 kg/m3, 6.448 MPa, and 1.372 MPa. The concrete blocks with the addition of AAT improved in mechanical properties compared to bricks without AAT.